The Impact of Palliative Medicine Consultation on Readmission Rates and Hospital Costs in Surgical Patients Requiring Prolonged Mechanical Ventilation - House, John S; Hyde, Carrie R; Corwin, Howard L; Harrington, Sarah E; Sexton, Kevin W; Karim, Saleema A; Kalkwarf, Kyle J; Jensen, Hanna K (Joint Commission journal on quality and patient safety, 2022)
The use of palliative care for critically ill hospitalized patients has expanded. However, it is still underutilized in surgical specialties. Postsurgical patients requiring prolonged mechanical ventilation have increased mortality and costs of care; outcomes from adding palliative care services to this population have been poorly investigated. The objective of this study was to determine the impact of palliative medicine consultation on readmission rates and hospitalization costs in postsurgical patients requiring prolonged mechanical ventilation. The Nationwide Readmissions Database was queried for adults (> 18 years) between the years 2010 and 2014 who underwent a major operation (Healthcare Cost and Utilization Project [HCUP] data element ORPROC = 1), required mechanical ventilation for ≥ 96 consecutive hours (ICD-9-CM V46.1), and survived until discharge. Among these, patients who received a palliative medicine consultation during hospitalization were identified using the ICD-9-CM diagnosis code V66.7. Of 53,450 included patients, 3.4% received a palliative care consultation. Compared to patients who did not receive a palliative care consultation, patients who did receive a consultation had a lower readmission rate (14.8% vs. 24.8%, p < 0.001) and lower average cost of hospitalization during the initial admission ($109,007 vs. $124,218, p < 0.001), findings that persisted after multivariable logistic regression. Utilization of palliative care in surgical patients remains low. Palliative care consultation in postsurgical patients requiring prolonged mechanical ventilation was associated with lower cost and rate of readmission. Further work is needed to integrate palliative care services with surgical care.